Thyroid-Stimulating Hormone-Stimulated Human Adipocytes Express Thymic Stromal Lymphopoietin - Ma, Loretta; Gagnon, AnneMarie; Landry, Anne; Le, Timothea; Xiao, Fengxia; Sun, Cathy; Lochnan, Heather A.; Burger, Dylan; Sorisky, Alexander (Hormone and Metabolic Research, 2018)
When recombinant human (rh) thyroid-stimulating hormone (TSH) is administered to thyroid cancer survivors, an acute extra-thyroidal effect raises pro-inflammatory cytokines and activates platelets. Thymic stromal lymphopoietin (TSLP) is a cytokine recently implicated in platelet activation. Our aim was to measure platelet microparticle levels after rhTSH stimulation in vivo, and to investigate TSLP expression in TSH-stimulated human adipocytes in culture. Blood samples for total and platelet microparticle analysis were obtained from thyroid cancer survivors before (day 1) and after rhTSH administration (day 5). Adipocytes, differentiated from stromal preadipocytes isolated from adipose tissue from surgical patients, were stimulated with TSH. TSLP mRNA expression, protein expression, and protein release into the adipocyte medium were measured. The level of platelet microparticles in thyroid cancer patients rose 5-fold after rhTSH stimulation. TSH upregulated TSLP mRNA expression in adipocytes in culture through a pathway that was inhibited by 66% by H89, a protein kinase A inhibitor. TSLP protein expression rose in response to TSH, and TSH-stimulated TSLP release into the medium was completely blocked by dexamethasone. In conclusion, TSLP is a novel TSH-responsive adipokine. Future studies will be needed to address the potential role of adipocyte-derived TSLP and whether it is linked to TSH-dependent platelet activation.
Keywords: cytokine; platelet; microparticles; protein kinase A